THU0127 IMMUNOGENICITY AND SAFETY OF 23-VALENT PNEUMOCOCCAL VACCINE IN PATIENTS WITH RHEUMATOID ARTHRITIS: RESULTS FROM 5-YEAR FOLLOW UP. (June 2019) - Bukhanova, Daria; Belov, Boris; Tarasova, Galina; Sergeeva, Marina; Muravyev, Yury; Lukina, Galina; Demidova, Natalia; Cherkasova, Maria
Abstract : Background: In rheumatology, comorbid infections have significant impact on patients' morbidity, mortality and quality of life. Prevention of infections is an integral part of supervision of these patients. Objectives: The aim of the study is to investigate immunogenicity and safety of 23-valent polysaccharide pneumococcal vaccine (PPV-23) in patients with rheumatoid arthritis (RA) in a five-years period. Methods: The study included 79 RA patients with ≥2 recent episodes of respiratory tract infections (bronchitis, pneumonia). 52 RA pts were treated with methotrexate (MT), 14 – with leflunomide (Lef), 13– with TNF- α inhibitors + MT. One dose (0, 5 ml) of PPV-23 was administered subcutaneously without discontinuing MT/Lef or 28-30 days prior to initiation of TNF- α inhibitors. Control visits were scheduled as follows: at baseline (Visit 1), and in 1, 3, and every year after immunization. 39 out of 110 pts were followed for 24 months, 23 pts – for 36 months, 23 pts – for 48 months, and 18 - for 60 months. Standard clinical examination and lab tests were performed at each visit. Levels of serum antibodies (AB) to Pneumococcal capsular polysaccharide were measured with VaccZymeTM PCP IgG 2 panels (The Binding Site Group Ltd, Birmingham, UK). Coefficient of post-immunization response (CPR) was determined for each patient as the ratio of AB levels at Visits II, III, IV, V, VI and VII to AB level at Visit I. Results: 53 (67%) patients did not have any reactions to the vaccine, 26 (33%) patients indicated pain, swelling and hyperemia of the skin (diameter up to 2 cm) at the injection site of the vaccine, low-grade fever. These typical reactions following vaccination are completely regressed within days without any additional treatment. They were not associated with RA therapy and did not require changes in ist schemes. Pronounced positive immune reaction to PPV-23 was documented in all RA patients on different therapeutic regimens as significant AB incremental growth. Significantly high level of post-immunization response still persisted after 4 and 5 years of follow-up.The proportion of responders to PPV-23 after 5 years reached 73% among RA patients. (Table). No case of clinically or radiographically confirmed pneumonia was documented during the follow up period, although one case of interstitial viral pneumonia was registered in 6 month after immunization. Not a single vaccination-related RA exacerbation episode or new autoimmune phenomenon was documented during the follow-up. *p<0, 05 Conclusion: Thus, all given prove the sufficient immunogenicity and safety of 23-valent pneumococcal vaccine in RA patients after 5 years of follow-up, getting different therapeutic regimens. Disclosure of Interests: None declared